Audiologic evaluation of vestibular schwannoma and other cerebellopontine angle tumors. (1st February 2016) - Kim, Sang Hoon; Lee, Sung Ho; Choi, Seok Keun; Lim, Young Jin; Na, Se Young; Yeo, Seung Geun
Abstract: Conclusion : Otologic accompanying symptoms, audiogram patterns, and hearing levels according to tumor size differed in patients with CPA tumors classified as VS and non-VS types. Objectives : The diagnosis of CPA tumors is often delayed. Late-diagnosed tumors can grow until they compress and damage vital structures. This study evaluated the otologic symptoms and results of audiologic tests in patients with vestibular schwannomas (VS) and other types of CPA tumors. Methods : This study included 171 patients with otologic symptoms who were diagnosed with CPA tumors, including 116 with VS and 55 with other types of CPA tumors. Factors analyzed retrospectively included tumor type, size, and location and the results of audiometric examinations. Results : The most common chief complaint in patients diagnosed with CPA tumors was asymmetrical hearing loss, with most frequent accompanying symptoms being tinnitus in patients with VS and dizziness in those with other types of CPA tumor. The most frequent patterns of hearing loss were the descending type in patients with VS and the flat type in patients with non-VS tumors ( p < 0.05). Pure tone thresholds tended to increase more in patients with VS than non-VS tumors according to tumor size, and pure tone averages were significantly higher in patients with VS than non-VS tumors of 11–25 mm in size ( p < 0.05).